2021
DOI: 10.4314/sajas.v50i5.9
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical models describing disappearance of Lucerne hay in the rumen using the nylon bag technique

Abstract: It is essential to study the dynamics of rumen degradation of feeds before their potential use in formulating diets for ruminants. Various mathematical models have been developed to describe this degradation. The non-lagged exponential model (Model I), the lagged exponential model (Model II), the Gompertz model (Model III), and the generalized Mitscherlich model (Model IV) were examined using two alternative software (SAS and MATLAB) to determine their efficacy in accounting for variation in ruminal disappeara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
(19 reference statements)
1
3
0
1
Order By: Relevance
“…Another study [ 34 ] showed that alfalfa hay had 56.1% of the slowly fermentable fraction, which is consistent with our findings. These achievements are in agreement with the reports of Palangi et al [ 23 ], who noted that the fermentation curves for legume forages vary according to their maturity and chemical composition. As previously discussed by Bayatkouhsar et al [ 35 ], cutting alfalfa in the afternoon as opposed to in the morning may result in higher concentrations of soluble carbohydrates, leaf content, and true protein, which may impact the fermentation pattern using the gas production method.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Another study [ 34 ] showed that alfalfa hay had 56.1% of the slowly fermentable fraction, which is consistent with our findings. These achievements are in agreement with the reports of Palangi et al [ 23 ], who noted that the fermentation curves for legume forages vary according to their maturity and chemical composition. As previously discussed by Bayatkouhsar et al [ 35 ], cutting alfalfa in the afternoon as opposed to in the morning may result in higher concentrations of soluble carbohydrates, leaf content, and true protein, which may impact the fermentation pattern using the gas production method.…”
Section: Resultssupporting
confidence: 93%
“…From the collected data using the in vitro approach, various mathematical models were created as prospective candidates to characterize the kinetics of feed fermentation. The behavior of the model was examined using the first-order kinetics model (without and with a lag phase) [ 23 ]. The mathematical definition is as follows:…”
Section: Methodsmentioning
confidence: 99%
“…In vitro DM degradation of treatments was measured in three replicate bottles. The percentage of degradability (Y) of DM over time (t) was described by the exponential equation: fitted to the data by iterative regression analysis (Palangi & Macit, 2019;Palangi et al, 2020). The effective degradability (ED) of DM and CP for feedstuffs was estimated as:…”
Section: Methodsmentioning
confidence: 99%
“…In this study, four different digestion models which has already been described by Palangi, Macit and Bayat. (2020) and were compared to investigate the digestion process.…”
Section: Gas Production In Vitro Degradation and In Vitro Digestibilitymentioning
confidence: 99%